2004
DOI: 10.1128/ec.3.5.1088-1100.2004
|View full text |Cite
|
Sign up to set email alerts
|

Introns and Splicing Elements of Five Diverse Fungi

Abstract: Genomic sequences and expressed sequence tag data for a diverse group of fungi (Saccharomyces cerevisiae, Schizosaccharomyces pombe, Aspergillus nidulans, Neurospora crassa, and Cryptococcus neoformans) provided the opportunity to accurately characterize conserved intronic elements. An examination of large intron data sets revealed that fungal introns in general are short, that 98% or more of them belong to the canonical splice site (ss) class (5GU. . .AG3), and that they have polypyrimidine tracts predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
265
1
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(303 citation statements)
references
References 69 publications
33
265
1
4
Order By: Relevance
“…Nearly 50% of S. pombe genes contain an intron, and almost half of those contain multiple introns (18,19). Moreover, the splice site sequences found within S. pombe introns do not conform to the tight consensus sequences seen in some other unicellular fungi, but rather are marked by a degeneracy more similar to that seen in human introns (20,21). Importantly, a single bona fide member of the serine/arginine-rich (SR) family of splicing regulators and several SR-like proteins implicated in the regulation of alternative splicing are encoded within the S. pombe genome (22,23).…”
mentioning
confidence: 99%
“…Nearly 50% of S. pombe genes contain an intron, and almost half of those contain multiple introns (18,19). Moreover, the splice site sequences found within S. pombe introns do not conform to the tight consensus sequences seen in some other unicellular fungi, but rather are marked by a degeneracy more similar to that seen in human introns (20,21). Importantly, a single bona fide member of the serine/arginine-rich (SR) family of splicing regulators and several SR-like proteins implicated in the regulation of alternative splicing are encoded within the S. pombe genome (22,23).…”
mentioning
confidence: 99%
“…Polymorphisms in the rDNA gene region have been attributed to small insertions/deletions, multiple duplications or, most often, to the presence of group-I introns. These introns are found in a diverse range of higher organisms, including fungi, protists and green algae, where they occur in the nuclear, mitochondrial and chloroplast genomes (Belshaw and Bensasson 2006;Bhattacharya et al 2005;Haugen et al 2005;Kupfer et al 2004;Mattick 1994).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in C. neoformans, preliminary analysis has shown that introns have a very tight distribution around 68bp and therefore, when annotating this genome, authors explicitly coded this 'spiked' intron length distribution in the TWINSCAN program instead of the default geometric distribution used in the original program (Tenney et al 2004). Kupfer et al (Kupfer et al 2004) provided the first comprehensive analysis of introns and splicing sites in five diverse fungi, which included the yeasts S. cerevisae and S. pombe; two well-studied Ascomycetes, A. nidulans and N crassa; and one Basidmycete, C. neoformans. Based on EST data they found that for all studied fungi more than 98% of all splice sites have the canonical 5'GT ... AG3' donor-acceptor pairs in agreement with vertebrate splice sites.…”
Section: Fungal Gene Structurementioning
confidence: 99%